Transplantation Immunology
DOI: 10.1385/1-59745-049-9:157
|View full text |Cite
|
Sign up to set email alerts
|

HLA Typing and Its Influence on Organ Transplantation

Abstract: Human leukocyte antigen (HLA) molecules are expressed on almost all nucleated cells, and they are the major molecules that initiate graft rejection. There are three classical loci at HLA class I: HLA-A, -B, and -Cw, and five loci at class II: HLA-DR, -DQ, -DP, -DM, and -DO. The system is highly polymorphic, there being many alleles at each individual locus. Three methods for HLA typing are described in this chapter, including serological methods and the molecular techniques of sequence-specific priming (SSP) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 21 publications
0
66
0
Order By: Relevance
“…The high rates of AR in LT and the weak effect of HLA matching to predict the development of rejection after transplant suggest that genetic risks for pulmonary allograft rejection are multifactorial. 22,23 In this study, we identified the CCL4L gene copy number as a genetic factor correlated with AR in LT. The CCL4L gene is located in a chromosome 17q12 copynumber-variable region that also includes the highly related CCL3L gene.…”
Section: Discussionmentioning
confidence: 91%
“…The high rates of AR in LT and the weak effect of HLA matching to predict the development of rejection after transplant suggest that genetic risks for pulmonary allograft rejection are multifactorial. 22,23 In this study, we identified the CCL4L gene copy number as a genetic factor correlated with AR in LT. The CCL4L gene is located in a chromosome 17q12 copynumber-variable region that also includes the highly related CCL3L gene.…”
Section: Discussionmentioning
confidence: 91%
“…The 1,774 MHC-SNPs evaluated here are a subset of 550,000 genome-wide SNPs recently characterized in our test population. MHCSNPs have been analyzed separately at first, to explore the utility of our statistical method, which is based in part on screening/testing approaches for quantitative traits proposed by others, by applying it to a candidate region with known impact in organ transplantation (14)(15)(16)(17). The results show that the minor allele G at the SNP locus rs9296068, which is significantly associated with rejection outcomes, localizes to the 5′ UTR (untranslated) region of the HLA-DOA gene.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical experience also supports this idea in that matched vascularized grafts survive better than unmatched grafts and the likelihood of survival increases the closer the alloantigen fit between recipient and donor. 16,17 Streilein et al 18 observed that corneal tissue lacked passenger leucocytes. Accordingly, both the lack of blood vessels and MHC Class II alloantigens accounted for the high acceptance rate of unmatched grafts.…”
Section: Sites Of Immune Privilegementioning
confidence: 99%